5(x-9)=-2 3=4(x+2) -7=5(x+5) 9=5(x+9) 7(x-1)=3x 9(x+7)=-x 5(x-3)=4x
5(x-9)=-2
3=4(x+2)
-7=5(x+5)
9=5(x+9)
7(x-1)=3x
9(x+7)=-x
5(x-3)=4x
Ответ(ы) на вопрос:
5x-45=-2; 5x=43; x=43/5=8.6
3=4x+8; 4x=-5;x=-5/4=-1.25
9=5x+45; 5x=-36;x=-7.2
7x-7=3x;4x=7; x=1.75
9x+63=-x;10x=-63;x=-6.3
5x-15=4x;x=15
5х-45=-2
5х=43
х=43/5
х=8 3/5
3=4х+8
4х=-5
х=-5/4
х=-1 1/4
-7=5х+25
5х=-32
х=-32/5
х=-6 2/5
9=5х+45
5х=-36
х=-36/5
х=-7 1/5
7х-7=3х
4х=7
х=7/4
х=1 3/4
9х+63=-х
10х=-63
х=-6,3
5х-15=4х
х=15
Не нашли ответ?
Похожие вопросы